Handbook of Relapsing-Remitting Multiple Sclerosis - Miller, Aaron (Springer International Publishing : Imprint: Adis, 2017)
This pocketbook is an evidence-based educational resource that provides a concise overview of diagnosis, treatment and long-term management of relapsing-remitting multiple sclerosis. An ideal clinical handbook for a wide range of medical professionals, this handbook includes international guidelines, clinically relevant clinical trial data, and an introduction to emerging therapies. Handbook of Relapsing-Remitting Multiple Sclerosis is a comprehensive overview of recent advances in this indication, enhanced by high quality figures and clinical images.
Keywords: Medicine.; Neurology.; elektronické knihy; electronic books